Evaluation of possibilities of the guard signalization complex with different number of seismic sensors near control area - Volochiі, B. Yu.; Zmysnyi, M.M.; Onyshchenko, V. A.; Salnyk, Yu. P.; Shkiluk, O. P. (Systems and Technologies, 2019)
The efficiency of guard signaling complexes (GSC), when a validity of clas-sification of moving objects (MO) is very important, is evaluated by the following indexes: probability of GSC task execution; probability of partial execution of the task; probability of user’s “deception”. Accordingly, the performance indicators of the GSC, in turn, depend on the indexes of the functionality of its constituents: probability of fixation of moving object by seismic sensor, probability of correct classification of MO type and probability of receiving radio signal by the system of receiving and displaying information (RDI). which crosses control zone, where three seismic sensors are installed, was devel-oped. Majority principle of identifying the type of moving object was used in the receiver of GSC. A comparative analysis of the efficiency of guard signaling complexes using one, two and three sensors in control zone are carried out.The GSC reaction is described by these procedures:Procedure 1 – detecting of moving object by seismic sensor. A moving ob-ject may be detected or not detected, however, the autonomous system of detec-tion, object classification and transmitting radio signals with seismic sensors in control zone, is workable. A moving object may not be detected in the following cases: it passed a seismic sensor at a safe distance; a moving object used special equipment that cannot be detected or was wearing special uniform; unsuitable place of seismic sensor location.Procedure 2 – classification of moving object. Alternative events are inher-ent in classification procedure, so can be performed correctly or incorrectly. The error in classification may be caused by corrupted method of processing seismic signal in autonomous system of detection, object classification and transmitting radio signals. Message with the result of MO classification is transmitted.Procedure 3 – delivering message with information about MO to system of RDI. The process of delivering radio signal about MO may be successful or not. Failure of message delivery to RDI may be caused by conditions of radio-wave transmission, presence of radio interference of natural and enemy-caused character.Procedure 4 – taking decision about type of moving object in RDI using ma-jority principle 2 out of 3.In the model of GSC reaction to MO control zone crossing it is taken into account the that a message about MO from different seismic sensors comes to SRDI not at the same time. That is why the process of forming states of majority element, where a corresponding decision is formed, has certain duration.A comparative analysis of the effectiveness of guard signaling complexes using one, two and three sensors in control zone are carried out.